A SOCIO PRAGMATICS ANALYSIS ON COMMANDING UTTERANCES IN THE OTHER BOLEYN GIRL MOVIE AND ITS TRANSLATION - KUSUMAWATI, FAJAR (2011)
This research is aimed to describe the variations of the language form, describe the equivalence of the implicature, and describe the equivalence of the politeness pattern on commanding utterances in The Other Boleyn Girl movie and its translation. In collecting the data, the writer uses documentation and observation method. The data are in the form of words, phrases and sentences which are used to proposed of commanding utterances and its translation. To clarify the form of commanding utterance and its translation, the writer refers to linguistics form theory. To describe the implicature of commanding utterances and its translation, the writer applies Grice theory, and to clarify the politeness strategies of commanding utterance and its translation, the writer employs four types of politeness strategy of Brown and Levinson. Having analyzed the data, the writer finds that the forms of commanding utterances and its translation are word is translated into word, phrase is translated into word, positive imperative sentence is translated into positive imperative sentence, negative imperative sentence is translated into negative imperative sentence, declarative sentence is translated into interrogative sentence, declarative sentence is translated into word, imperative sentence is translated into word, positive imperative sentence is translated into negative imperative sentence, declarative sentence is translated into declarative sentence, imperative sentence with tag question is translated into imperative sentence, declarative sentence with tag question is translated into imperative sentence, and interrogative sentence is translated into interrogative sentence. The implicatures use on commanding utterances and its translation are conversational implicature and conventional implicature in the form of equivalent and non equivalent. The politeness strategies use on commanding utterances and its translation are bald on record, positive politeness, and negative politeness strategy in the form of equivalent and non equivalent.